Facile fabrication of platinum loaded poly(2, 5-dimethoxy aniline)/activated carbon ternary nanocomposite as an efficient electrode material for high performance supercapacitors. (April 2023) - Dhanusuraman, Ragupathy; Chahal, Priyanka; Raveendran, Asha; Hossain, Maimur; Alshgari, Razan A.; Wabaidur, Saikh Mohammad; Eswaran, Muthusankar
Abstract: This article details the fabrication of conductive Pt@PDMA/AC nanocomposite via layer by layer electrochemical deposition process on a flexible current collector for highly effective flexible supercapacitor. The unique nanostructure and crystallinity were characterized by using scanning electron microscope (SEM), transmission electron microscopy (TEM) and X-ray diffraction. These suggested electrodes make the most of their incredible electrical conductivity, mechanical strength, electrochemical stability, and adherence to a flexible current collector. They also exhibit great capacitive performance and exceptional cycle life. The Pt@ PDMA/AC electrode has contributed to a good specific capacitance of 348.48 F/g at current density 1 A/g. Further, the nanocomposite shows remarkable stability where 95 % of its capacity retained after 3000 cycles at 10 A/g. due to synergetic effects. The final nanocomposite contributes to a maximum energy density of 108.9 Whkg −1 at the power density of 2840.86 Wkg −1 at 1 A/g current density. The resulting nanocomposite is a strong contender for energy storage and flexible electronic devices due to its outstanding electrochemical characteristics and great cycle stability. Graphical abstract: Unlabelled Image Highlights: Pt@PDMA/AC electrode fabricated via layer by layer electrochemical deposition. Pt@PDMA/AC electrode has good specific capacitance of 348.48 F/g at current density 1 A/g. Nanocomposite shows stability of 95% and capacity retained after 3000 cycles at 10 A/g. It shows energy density of 108.9 Whkg -1 at the power density of 2840.86 Wkg -1 at 1 A/g current density.